Recurrent uterine tumors resembling ovarian sex-cord tumors with the growth regulation by estrogen in breast cancer 1-nuclear receptor coactivator 2 fusion gene: a case report and literature review - Bin Chang; Qianming Bai; Lin Liang; Huijuan Ge; Qianlan Yao (BMC, 2020)
Abstract Background Uterine tumors resembling ovarian sex-cord tumors (UTROSCTs) are rare mesenchymal neoplasms predominantly arising in perimenopausal and postmenopausal women. UTROSCTs with growth regulation by estrogen in breast cancer 1 (GREB1)-rearrangement or GREB1-rearranged uterine tumors are exceptionally rare, with only 12 previously reported cases. Here, we report a case of UTROSCT with the GREB1-nuclear receptor coactivator 2 (NCOA2) fusion gene. Case presentation A 57-year-old woman presented with a 10.0 cm uterine mass. The tumor was composed of short spindle or epithelioid cells, arranged in diffused sheets, nested, and trabecular/cordlike. The tumor harbored the GREB1-NCOA2 fusion gene, as confirmed by RNA sequencing. The tumor recurred in the pelvis at 30 months after the initial diagnosis. We also compared the clinical and pathologic features of this case with those of the 12 previously published uterine GREB1-rearranged tumors. Of the combined 13 cases (present case and 12 previous cases), the mean age of patients was 64.8 years (range, 51-74 years). Of the nine reported cases of GREB1-rearranged tumor with follow up, four cases recurred or metastasized (44.4%). Microscopically, most tumors (10/12, 83.3%) showed infiltrative growth, and two were well demarcated. Mitotic figures ranged from 0 to 14 per 10 high-power fields (2 mm2; mean: 3.6). Lymphovascular invasion and necrosis were each present in two cases (2/12, 16.7% and 2/7, 28.6%, respectively). Conclusions This case provided further evidence that UTROSCTs with GREB1-rearrangement may have a high risk of recurrence/metastasis. Further studies are necessary to clarify the clinical features of this type of tumor, particularly the prognosis, potential treatment, and range of possible molecular events.